The Primer Design and Optimization of Annealing Temperature for Analysis of Glutathione Reductase Gene Expression in Rice (Oryza sativa L.) - Annisa Khaira; Afifatul Achyar; Zulyusri Zulyusri; Yusni Atifah; Dwi Hilda Putri; Violita Violita (3BIO: Journal of Biological Science, Technology and Management, 2023)
Glutathione Reductase (GR) belongs to the NADPH-dependent flavoprotein oxidoreductase family and is found in both prokaryotes and eukaryotes. The GR gene is considered to play a key role in the elimination of oxidative reaction products by looking at the level of gene expression of GR rice in dealing with  drought stress using qPCR. One of the important steps to develop a specific, effective and efficient qPCR is the primer design. Several studies analyzing GR gene expression in rice have also designed primers. However, the primer still lacks an ideal characteristic of primer, as it still has a secondary structure. This studies aims to design rice GR specific primers and optimize the annealing temperature for GR gene expression analysis on rice. Primers were designed using the  Primer3 and Geneious Prime and checked for specificity using the Primer-BLAST tool. The selected primer pairs were then optimized for annealing  temperature using gradient PCR. The best primer design results were GR-Forward 5’-ACGATTGCAGCCAGTGAAGA-3’ and GR-Reverse 5’-TGCGGCAATACTATCAACATCC-3’, with an amplicon length of 204 bp, primer base lengths of 20 and 22 nucleotides, Tm values of 60°C and 58.9°C, %GC of 50% and 45.5%, respectively. This primer pair had no secondary structure, both hairpin and self dimer. Gradient PCR showed the optimum annealing temperature for this primer pair was 52.2oC so that the primer can be used as a specific primer to analyze  the GR gene expression in rice using qPCR.